Studium generale in Zadar in the context of the universities expansion programme in Europe in the 14th century - Krasić, Stjepan (2024)
The work examines the context of the establishment of the University of Zadar in 1396 and the specialized terminology used for institutions of that rank. In literature and among some segments of the public, there are misunderstandings and misinterpretations regarding the development of higher education in Europe during the late Middle Ages. This work aims to clarify doubts concerning the rank and functioning of higher education in Zadar from the late 14th to the early 19th century.It consists of three main chapters. The first chapter, "Medieval Universities and Their Historical-Legal Terminology," focuses on the beginnings and development of the first forms of higher education in Italy and France. The second chapter, "The Establishment of the General University in Zadar within the Political and Cultural Movements of the 14th Century," discusses the historical, political, and cultural relations between Croatia and neighboring Italy, which culminated in 1396 with the establishment of the first institution of higher education in Croatian territory: the general university in Zadar. The third chapter, titled "The Nature and Structure of the General University in Zadar," which had two faculties (philosophical and theological), analyzes the composition of the community of professors and students with their own associations.This manuscript is the culmination of many years of diligent research by a distinguished and experienced expert in the history of the Dominican Order among Croats, who enjoys great respect among European (especially Italian) historians. It is important to emphasize that this manuscript contains a comprehensive text that allows for a better understanding of the earliest history of education in Zadar and central Dalmatia, which will undoubtedly stimulate further research on this seemingly narrow topic, deserving of greater attention both within a specialized circle (history, pedagogy) and in the broader community interested in socio-cultural, ecclesiastical, intellectual, heritage, and identity issues.